Application of PDE Constrained Optimization in Internal Combustion Engine Pollution Control - Hongliang Guan (Journal of Mathematics)
Aiming at the problem of secondary pollution of waters due to the difficulty of controlling the dosage of purifiers in the treatment of internal combustion engine pollution, a partial differential equation (referred to as PDE) constrained optimization algorithm based on l1-norm is proposed. The algorithm first converts the internal combustion engine control model of the scavenger dose into a constrained optimization problem with a l1-penalty term. Secondly, it introduces a dose constraint condition based on PDE and uses the inherent property of Moreau-Yosida regularization to establish a smooth minimization function. Finally, the semismooth Newton method is used to iteratively find the optimal solution. The results of the comparison experiment show that the algorithm in this paper has a great improvement in the results of Newton step number and dose area percentage.